2019
DOI: 10.1111/jipb.12745
|View full text |Cite
|
Sign up to set email alerts
|

GW5‐Like, a homolog of GW5, negatively regulates grain width, weight and salt resistance in rice

Abstract: Grain size is an important determinant of yield potential in crops. We previously demonstrated that natural mutations in the regulatory sequences of qSW5/GW5 confer grain width diversity in rice. However, the biological function of a GW5 homolog, named GW5‐Like (GW5L), remains unknown. In this study, we report on GW5L knockout mutants in Kitaake, a japonica cultivar (cv.) considered to have a weak gw5 variant allele that confers shorter and wider grains. GW5L is evenly expressed in various tissues, and its pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 42 publications
2
20
1
Order By: Relevance
“…Subcellular localization, biochemical function and positive role of the GW5L protein in the BR signaling regulation are similar to those of the domestication-related GW5 homolog [88]. Moreover, the GW5 and GW5L proteins may also be involved in the salt-stress reaction through interaction with the calmodulin protein OsCaM1-1 which is a positive regulator of the salt stress tolerance [88,89]. It was suggested that GW5 and GW5L may directly or indirectly repress transcription of the OsCaM1-1 gene.…”
Section: Regulation Of the Br Signaling Relay In Monocotsmentioning
confidence: 86%
See 1 more Smart Citation
“…Subcellular localization, biochemical function and positive role of the GW5L protein in the BR signaling regulation are similar to those of the domestication-related GW5 homolog [88]. Moreover, the GW5 and GW5L proteins may also be involved in the salt-stress reaction through interaction with the calmodulin protein OsCaM1-1 which is a positive regulator of the salt stress tolerance [88,89]. It was suggested that GW5 and GW5L may directly or indirectly repress transcription of the OsCaM1-1 gene.…”
Section: Regulation Of the Br Signaling Relay In Monocotsmentioning
confidence: 86%
“…Therefore, both GW5 and GW5L may act as regulators of grain size and the salt-stress tolerance in rice (Figure 1). It was suggested that the GW5 and GW5L homologs may serve as candidates for genetic manipulation through targeted genome editing to improve grain yield and salt-stress tolerance in rice and perhaps in other cereals [44,88].…”
Section: Regulation Of the Br Signaling Relay In Monocotsmentioning
confidence: 99%
“…While these functions are diverse, no coherent mechanistic framework has emerged for the cellular basis underlying the altered morphology. Importantly, although GW5 and GW5 like (GW5L, Tian et al , ) share similarities with OsIQD14 regarding sequence and control of seed shape, both GW5 and GW5L are plasma membrane‐localized protein involving in brassinosteroid signalling by regulating BIN2 activity. In contrast, we identified OsIQD14 as a key regulator of grain shape by acting on cell shape determination through controlling the MT cytoskeleton, making this a novel target for breeding approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A few already reported genes in rice were co-located with the heterotic QTLs identified in this study such as qGYP10.1 ( OsPQT3 , increases grain yield in the field) 49 , qPN9.2 and qTGW9 ( OsCCC1 for cell elongation and panicle number 50 , OsTb2 for tillering and grain yield per panicle 51 , and Oshox4 affecting bushy tillers 52 , OsZHD1 for tiller number 53 , and OsEATB , ERF protein associated with tillering and panicle branching 54 , qTGW1.1 ( GW5L , negatively regulates grain width and weight) 55 , qTGW2.2 ( OsGS1 , growth rate and grain filling) 56 , qTGW3.3 ( GS3 , grain length and weight) 57 , qTGW3.6 ( OsMADS34 , grain size and yield 58 , Pho1 , the size of mature seeds and the starch content) 59 , and qTGW6.1 ( OsKASI , 1000-grain weight and tiller number) 60 . All the above mentioned genes provided heterotic effects with heterozygous alleles in UD-type or D-type M-QTLs.…”
Section: Discussionmentioning
confidence: 72%